An Analysis of Higher-Order Thinking Skill Questions in Reading Exercises of Pathway to English (2022 Edition) for the Tenth Grade of Senior High School - Iqbal Fathoni C Sihombing; Fitrawati Fitrawati (Universitas Negeri Padang, 2023)
This research aimed to analyze Higher-Order Thinking Skill (HOTS) questions in reading exercises of the Pathway to English textbook for the tenth grade of senior high school. Higher-Order Thinking Skill (HOTS) refers to advanced cognitive abilities that involve analyzing, evaluating, and creating, which are the three levels of thinking in the revised Bloom's taxonomy. This research employed a quantitative descriptive design. The researcher collected data from the textbook and used a checklist table to gather a list of questions. The researcher used Revised Bloom's Taxonomy indicators to categorize the reading questions. The results showed that the total number of HOTS questions was 73 or 28.74% out of 254 reading questions. Then, the total for each HOTS level question was 37 questions or 14.56% for the Analyzing level, 29 questions or 11.41% for the Evaluating level, and seven questions or 2.75% for the Creating level. The total number of LOTS questions was 181 or 71.26% out of 254 reading questions. The percentage of Higher-Order Thinking Skill (HOTS) questions was lower than the total Lower-Order Thinking Skill (LOTS) questions. However, the percentage of HOTS levels in this textbook, which adopts the Merdeka Curriculum, is higher than in textbooks adopting the previous curriculum, the 2013 Curriculum.